LANGUAGE VARIATION IN TERM OF MIXING CODE IN KISARASA YOUTUBE CHANNEL - Wesdayanti, Ni Made (ID Solutions, 2024)
The study of sociolinguistics revolves around the ways in which language and society, along with the cultural variables that influence them, interact. In modern times, the capacity to speak more than one language has had an impact on the way people interact with one another in society. The occurrence of this phenomena results in the utilization of code mixing in words or utterances. The purpose of this study is to present and examine the many forms of language mixtures that may be found in Kisarasa videos that are uploaded to YouTube channels. In order to collect data, this study employs a descriptive-qualitative methodology. Additionally, listening and recording techniques are utilized in order to obtain comprehensive data results. In order to determine the various sorts of code mixing, this research makes use of Hoffman's (1991) theory. The findings that were collected demonstrate the many types of code mix, including intra-sentential and intra-lexical code mix, as well as code mix that involves a change in pronunciation.